1. (x+3)kwadrat + 6(x+3)=162. (3x+2)(x-1)-13=2x(2-x)3. 9(x-4)kwadrat + 4(x-4)=04. (y+3)(y+2)=1-y
(x+3)(x+3) +6x+18=16x^2+3x+3x+9 +6x+18 -16 =0x^2+12x-11=0delta= b^2-4acd= 12^- 4*1*(-11)
d= 144+44d = 188d= pod pierwiastkiem 1883x^2-3x+2x-2-14-4x-2x=03x ^2-7x-16=0delta= b^2-4acd= 7^2- 4 * 3 * (-16)d= 49+192d= 241 d= 241 pod pierwiastkiem9(x-4)(x+4) +4x -16=09 ( x^2 +4x-4x) +4x -16 = 09x^2 + 36x -36x + 4x - 16 = 09x^2 + 4x -16= 0delta= 16 - 36 ( - 16 )d= 592d= 592 pod pierwiastkiemy^2+2y+3y+6-1+y=oy^2+6y -5 = 0delta= 36 - 4 ( -20)d= 2880d= 2880 pod pierwiastkiem
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
(x+3)(x+3) +6x+18=16
x^2+3x+3x+9 +6x+18 -16 =0
x^2+12x-11=0
delta= b^2-4ac
d= 12^- 4*1*(-11)
d= 144+44
d = 188
d= pod pierwiastkiem 188
3x^2-3x+2x-2-14-4x-2x=0
3x ^2-7x-16=0
delta= b^2-4ac
d= 7^2- 4 * 3 * (-16)
d= 49+192
d= 241
d= 241 pod pierwiastkiem
9(x-4)(x+4) +4x -16=0
9 ( x^2 +4x-4x) +4x -16 = 0
9x^2 + 36x -36x + 4x - 16 = 0
9x^2 + 4x -16= 0
delta= 16 - 36 ( - 16 )
d= 592
d= 592 pod pierwiastkiem
y^2+2y+3y+6-1+y=o
y^2+6y -5 = 0
delta= 36 - 4 ( -20)
d= 2880
d= 2880 pod pierwiastkiem